Status of the lunar detection mode for cosmic particles of LOFAR - Winchen, T.; Bonardi, A.; Buitink, S.; Corstanje, A.; Falcke, H.; Hare, B. M.; Hörandel, Jörg R.; Mitra, P.; Mulrey, K.; Nelles, Anna; Rachen, J. P.; Rossetto, L.; et al. (Journal of Physics: Conference Series, 2019)
Cosmic particles hitting Earth's moon produce radio emission via the Askaryan effect. If the resulting radio ns-pulse can be detected by radio telescopes, this technique potentially increases the available collective area for ZeV scale particles by several orders of magnitude compared to current experiments. The LOw Frequency ARray (LOFAR) is the largest radio telescope operating in the optimum frequency regime for this technique. In this contribution, we report on the status of the implementation of the lunar detection mode at LOFAR.
CRIS-Team Scopus Importer:2023-08-15